Domain formation in DODAB–cholesterol mixed systems monitored via nile red anisotropy - Hungerford, Graham (2005)
The effect of the cholesterol (Ch) on liposomes composed of the cationic lipid dioctadecyldimethylammonium bromide (DODAB) was assessed by studying both the steady-state and time-resolved fluorescence anisotropy of the dye Nile Red. The information obtained combined with analysis of the steady-state emission and luorescence lifetime of Nile Red (NR) for different cholesterol concentrations (5–50%) elucidated the presence of “condensed complexes” and cholesterol-rich domains in these mixed systems. The steady-state fluorescence spectra were decomposed into the sum of two lognormal emissions, emanating from two different states, and the effect of temperature on the anisotropy decay of Nile Red for different cholesterol concentrations was observed. At room temperature, the time-resolved anisotropy decays are indicative of NR being relatively immobile (manifest by a high r∞ value). At higher temperature, rotational times ca. 1 ns were obtained throughout and a trend in increasing hindrance was seen with increase of Ch content.